THE INFLUENCE OF INTERNATIONAL ASSOCIATIONS AND PROFESSIONAL UNIONS OF THE ORGANIZATION OF BUSINESS TOURISM ON THE DEVELOPMENT OF THE TOURISM INDUSTRY - PANOVA, Iryna; SIDOROV, Mykhailo; PUZANOV, Andriy (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The influence of international associations and professional unions on the development of the tourism industry is a key aspect in its modern dynamics. Business tourism, or corporate tourism, is an important component of the tourism industry, which plays a significant role in the global economy and society. International associations and professional unions create a foundation for cooperation and coordination in this field, contributing to the creation of standards, the development of innovations and the improvement of the quality of services. It is noted that one of the key organizations influencing business tourism is the World Tourism Organization (UNWTO), which is the main global body promoting the development and regulation of the tourism industry. It has been studied that the influence of international associations and professional unions on business tourism consists in increasing the competitiveness and efficiency of the industry. They contribute to the development of infrastructure, the creation of new tourism products, the introduction of innovations and ensure the balanced development of the industry in different regions of the world. In addition, they influence the formation and implementation of tourism policies, which contributes to the sustainable development of the sector. It is substantiated that international associations and trade unions play an indispensable role in the development of the tourism industry, in particular in the field of business tourism. Their influence is manifested in the creation of standards, regulation, development of innovations, improvement of the quality of services and support of sustainable growth of the tourism industry. They contribute to the creation of an enabling environment for businesses operating in the industry and help them adapt to changes in the global tourism environment. It was highlighted that international associations and trade unions are actively cooperating with government bodies and other interested parties to resolve significant issues related to business tourism. They can influence the formation and implementation of tourism policies, which contributes to the sustainable growth of the sector and provides a favorable climate for business.